2019
DOI: 10.1016/j.stemcr.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Modeling of Neuroferritinopathy Reveals Iron as a Determinant of Senescence and Ferroptosis during Neuronal Aging

Abstract: Neuroferritinopathy (NF) is a movement disorder caused by alterations in the L-ferritin gene that generate cytosolic free iron. NF is a unique pathophysiological model for determining the direct consequences of cell iron dysregulation. We established lines of induced pluripotent stem cells from fibroblasts from two NF patients and one isogenic control obtained by CRISPR/Cas9 technology. NF fibroblasts, neural progenitors, and neurons exhibited the presence of increased cytosolic iron, which was also detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…The toxic potential of excess iron lies in its ability to generate reactive oxygen species,10 which damage DNA,11 irreversibly modify proteins via highly reactive aldehydes12 and stimulate release of iron from storage proteins leading to generation of further reactive oxygen species 5. This can ultimately end in iron-mediated cell death 13. Excess brain iron is also important in key pathophysiological pathways specific to PD 9.…”
Section: Introductionmentioning
confidence: 99%
“…The toxic potential of excess iron lies in its ability to generate reactive oxygen species,10 which damage DNA,11 irreversibly modify proteins via highly reactive aldehydes12 and stimulate release of iron from storage proteins leading to generation of further reactive oxygen species 5. This can ultimately end in iron-mediated cell death 13. Excess brain iron is also important in key pathophysiological pathways specific to PD 9.…”
Section: Introductionmentioning
confidence: 99%
“…The latter results in cells either activating the molecular network (which could be seen as a self-defense response) or, as an alternative, increasing their death by ferroptosis. A recent study demonstrated that human fibroblasts and neurons exposed to non-ferritin-dependent iron undergo both cell senescence and cell death by ferroptosis, suggesting that iron is a key player in the mechanisms leading to aging and neurodegeneration [ 118 ]. CRISPR/Cas9 technology was employed to obtain induced pluripotent stem cells (iPSC) from neuroferritinophaty (NF) patients.…”
Section: Molecular Mechanisms Of Adult Stem Cell Senescence and Agmentioning
confidence: 99%
“…It can inhibit glutathione peroxidase 4 (GPx4) and delete the corresponding GPx4 gene to cause glutathione depletion. As such, cellular LPO accumulates in phospholipids containing polyunsaturated fatty acids [22][23][24]. Cellular Fe 2+ catalyzes the conversion of LPO to LOO • , which directly triggers cell death [5,[25][26][27][28][29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%